1967
DOI: 10.1039/j39670001720
|View full text |Cite
|
Sign up to set email alerts
|

Applications of high-potential quinones. Part I. The mechanism of dehydrogenation of steroidal ketones by 2,3-dichloro-5,6-dicyanobenzoquinone

Abstract: The reaction of 2.3-dichloro-5.6-dicyanobenzoquinone with steroidal 4-en-3-ones is catalysed by acids. 1.2-Dehydrogenation predominates in the presence of weak acids, as it does in the uncatalysed reaction, whereas strong acids promote exclusive formation of 6,7-dehydro-derivatives. These results are rationalised by a mechanism involving oxidation of the alternative enolic forms of the ketone. Thus, in the absence of acid or with weak acids, the kinetically determined 2.4-dien-3-01 undergoes C-1 hydride ion ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 0 publications
0
29
1
1
Order By: Relevance
“…[14] The dehydrogenation of 8 and 9 with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) when catalyzed by acid [15] proceeded slowly, but cleanly, to provide enediones 6 and 7 (Scheme 1). Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…[14] The dehydrogenation of 8 and 9 with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) when catalyzed by acid [15] proceeded slowly, but cleanly, to provide enediones 6 and 7 (Scheme 1). Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…For the introduction of the 1,4-diene system into the A-ring of 7, we decided to use the one-pot operation employing 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ). 7 DDQ has been extensively employed in steroid chemistry avoiding the use of halogens and selenium reagents. 8 We choose to use DDQ over the palladium-catalyzed process to dehydrogenate carbonyl enol ethers 9 because we found the one-pot DDQ procedure to be more chemoselective.…”
Section: Resultsmentioning
confidence: 99%
“…In this case it involves a (benzylic) hydride transfer from compounds 10aϪc to DDQ, and the presence of an electrondonating substituent in the phenyl ring should stabilise the formed carbocation (C-3ЈЈ). In an attempt to optimise the experimental procedure we found that the presence of a small amount (20% molar equivalent) of p-toluenesulfonic acid [16] resulted in faster formation of the expected 5-(2-hydroxyphenyl)-3-naphthylpyrazoles 12aϪc with slightly improved reaction yields (Table 1, Scheme 1, E, Method B).…”
Section: Introductionmentioning
confidence: 96%
“…Only in the oxidation of 3-(2-hydroxyphenyl)-5-{2-[3-(4-methoxyphenyl)]-1,2,3,4-tetrahydronaphthyl}pyrazole (9b) with five molar equivalents of DDQ at reflux in dry 1,4-dioxane in the presence of a small amount (20% molar equivalent) of p-toluenesulfonic acid [16] did we succeed in isolating and characterising…”
Section: Introductionmentioning
confidence: 99%